Detection of anorectal and cervicovaginal Chlamydia trachomatis infections following azithromycin treatment: prospective cohort study with multiple time-sequential measures of rRNA, DNA, quantitative load and symptoms. - Nicole H T M Dukers-Muijrers (Public Library of Science (PLoS), 2013)
Background Determination of Chlamydia trachomatis (Ct) treatment success is hampered by current assessment methods, which involve a single post-treatment measurement only. Therefore, we evaluated Ct detection by applying multiple laboratory measures on time-sequential post-treatment samples. Methods A prospective cohort study was established with azithromycin-treated (1000 mg) Ct patients (44 cervicovaginal and 15 anorectal cases). Each patient provided 18 self-taken samples pre-treatment and for 8 weeks post-treatment (response: 96%; 1,016 samples). Samples were tested for 16S rRNA (TMA), bacterial load (quantitative PCR; Chlamydia plasmid DNA) and type (serovar and multilocus sequence typing). Covariates (including behavior, pre-treatment load, anatomic site, symptoms, age, and menstruation) were tested for their potential association with positivity and load at 3-8 weeks using regression analyses controlling for repeated measures. Findings By day 9, Ct positivity decreased to 20% and the median load to 0.3 inclusion-forming units (IFU) per ml (pre-treatment: 170 IFU/ml). Of the 35 cases who reported no sex, sex with a treated partner or safe sex with a new partner, 40% had detection, i.e. one or more positive samples from 3-8 weeks (same Ct type over time), indicating possible antimicrobial treatment failure. Cases showed intermittent positive detection and the number of positive samples was higher in anorectal cases than in cervicovaginal cases. The highest observed bacterial load between 3-8 weeks post-treatment was 313 IFU/ml, yet the majority (65%) of positive samples showed a load of ≤ 2 IFU/ml. Pre-treatment load was found to be associated with later load in anorectal cases. Conclusions A single test at 3-8 weeks post-treatment frequently misses Ct. Detection reveals intermittent low loads, with an unknown risk of later complications or transmission. These findings warrant critical re-evaluation of the clinical management of single dose azithromycin-treated Ct patients and fuel the debate on defining treatment failure. Clinicaltrials.gov Identifier: NCT01448876.